A simple and modular MIMO antenna system for closely spaced patch antennas. Issue 7 (11th April 2022) - Abbasi, Muhammad Nawaz; Aziz, Abdul; Malik, Waqar A.; Chishti, Abdul Rehman; Hussain, Rifaqat
Abstract: A simple, low cost and modular decoupling technique is proposed to achieve high isolation between very close antenna elements of a multiple‐input‐multiple‐output (MIMO) system without any complex decoupling structure, vias, or defected ground structure (DGS). A rectangular thin parasitic strip is used to decouple square patch elements, which are separated by an extremely close distance of 0.018 λ $0.018\unicode{x02007}λ $ at 6 $6$ GHz. The proposed technique has achieved more than 40 $40$ dB isolation between MIMO antenna elements with a minimum return loss of 22 $22$ dB. A straightforward three‐step method is also proposed to shift the resonance frequency to some other frequency with similar isolation and impedance matching. All the important characteristics and performance parameters of the proposed design technique are analyzed, simulated, and verified through the measurement of the fabricated prototype.